Development of mouza level databases of potato in Munshigong, Bogra & Rangpur district - Uddin, MA; Rahman, KS; Rahman, MM; Mohammad, N; Nasrin, S (Bangladesh Journal of Agricultural Research, 2016)
A study was conducted to build the mouza and union level databases of potato during 2011-12 using both primary and secondary data. Primary data were collected from potato growers of unions of three upazilas, namely Vober Char, (Gazaria, Munshigonj), Atmul, (Shibganj, Bogra) and Mittipur (Pirganj, Rangpur), respectively. Mouza, union, upazila and district level digitized maps of Bangladesh were used in the program. GIS, GPS, MIS, Modem and mobile phone technologies were used. Databases of different parameters such as area, production, yield, and varietal information etc. of potato were obtained. Mouza have been used as the smallest unit of land use management for agriculture because it has administrative boundary and social identity. Average yield of potato was 17.45 t/ha in the study areas during 2011-12. Out of total potato areas 69.06% was cultivated by HYVs and the rest 30.94% by local varieties. Out of 46 HYVs released by BARI, 11 varieties were cultivated in the study areas during the same period. Databases and maps developed by data collection from root level (Farmers field, mouza, block and union etc.) may help to identify variety wise area coverage of potato. Bangladesh J. Agril. Res. 41(2): 353-364, June 2016